AB1199 COST-EFFECTIVENESS OF EARLY INITIATION OF ABATACEPT ON JAPANESE RHEUMATOID ARTHRITIS PATIENTS BASED ON THE AMPLE STUDY, USING IORRA REAL WORLD DATA. (2nd June 2020) - Tanaka, E.; Inoue, E.; Shoji, A.; Nilsson, J.; Papagiannopoulos, C.; Devender, D.; Anazawa, Y.; Yoshizawa, Y.; Harigai, M.
Abstract : Background: Rheumatoid arthritis (RA) is a chronic inflammatory disorder leading to disability and reduced quality of life. Effective treatment with biologic disease-modifying antirheumatic drugs (bDMARD) poses a significant economic burden. The abatacept (ABT) versus adalimumab comparison in biologic-naive RA subjects with background methotrexate (AMPLE) trial 1 was a head-to-head randomized study. Objectives: To assess the cost-effectiveness (CE) of early initiation of ABT on Japanese RA patients with data from the IORRA database (ID). 2 Methods: A model based on the AMPLE study was used to estimate the CE of ABT 1 st versus ABT 2 nd lines in a cohort of 1000 patients based on responses on ACR20/50/70, HAQ-DI, CDAI and SDAI estimated from the real-clinical data of the ID. Unit costs for direct medical costs of adverse events (AEs), proportions of patients with concomitant medications or outpatient/inpatient visits; doses and duration of concomitant medications were taken from the JMDC claims database. 3 Uncertainty was assessed in sensitivity analyses (SA) where cost parameters were tested on their ±30% levels. Results were compared between subgroups using cut-offs of 65-years of age and 1.5 of HAQ, or 5-years of treatment duration. The study used a Japanese healthcare payers' perspective over a 2-year time horizon. Results: Incremental costs were all in favor of ABT 2 nd line with 137 MJPY (1.1 M€, 120 JPY=1 €), 6 MJPY (0.05 M€), 41 MJPY (0.3 M€), 8 MJPY (0.07 M€) and 2.2 MJPY (0.02 M€) for bDMARDs, concomitant medication, AEs, serious AE, and hospitalizations due to infections, respectively. In total, the incremental costs were expected to be 195 MJPY (1.6 M€) higher for ABT as 1 st line treatment, but the cost per responding patient and per patient in remission favored ABT 1 st line across most response outcomes (Table 1 ). SA showed that the cost for bDMARDs drives the difference in healthcare costs between the cohorts (-685 MJPY to 1, 074 MJPY). For sub-groups of patients ≥65 years, <65 years, HAQ≥1.5, HAQ <1.5, treatment duration ≥5 years, <5 years the total 2-yearly costs per responder (SDAI remission) were 106 kJPY (0.9 k€), 321 kJPY (2.7 k€), 1, 353 kJPY (11.3 k€), 106 kJPY (0.9 k€), 231 kJPY (1.9 k€) and 178 kJPY (1.5 k€) lower for ABT 1 st line, respectively. Conclusion: Savings per responding patient are expected if ABT are prescribed as 1 st line versus 2 nd or 3 rd line treatment, irrespective of age, disease duration and functional impairment level. References: [1]Sokolove J MS et al., Anna rheum dis. 2015;74(Suppl 2) [2]IORRA cohort database, Tokyo Women's Medical University, Tokyo, Japan [3]JMDC claims database, Tokyo, Japan Disclosure of Interests: Eiichi Tanaka Consultant of: ET has received lecture fees or consulting fees from Abbvie, Asahi Kasei pharma co., Bristol Myers Squibb, Chugai Pharmaceutical, Daiichi Sankyo Co., Eisai Pharmaceutical, Janssen Pharmaceutical K.K., Nippon Kayaku, Pfizer, Takeda Pharmaceutical, Taisho Toyama Pharmaceutical Co., and UCB Pharma., Speakers bureau: ET has received lecture fees or consulting fees from Abbvie, Asahi Kasei pharma co., Bristol Myers Squibb, Chugai Pharmaceutical, Daiichi Sankyo Co., Eisai Pharmaceutical, Janssen Pharmaceutical K.K., Nippon Kayaku, Pfizer, Takeda Pharmaceutical, Taisho Toyama Pharmaceutical Co., and UCB Pharma., Eisuke Inoue Speakers bureau: EI has received speaker fee from Bristol-Meyers, Pfizer, Merck serono., Ayako Shoji Consultant of: To conduct this work, Jonas Nilsson Consultant of: To conduct this study, Christos Papagiannopoulos Consultant of: To conduct this study, Dhanda Devender Shareholder of: BMS, Employee of: BMS, Yoshio Anazawa Shareholder of: BMS, Employee of: BMS, Yuri Yoshizawa Shareholder of: BMS, Employee of: BMS, masayoshi harigai Grant/research support from: AbbVie Japan GK, Ayumi Pharmaceutical Co., Bristol Myers Squibb Co., Ltd., Eisai Co., Ltd., Mitsubishi Tanabe Pharma Co., Nippon Kayaku Co., Ltd., and Teijin Pharma Ltd. MH has received speaker's fee from AbbVie Japan GK, Ayumi Pharmaceutical Co., Boehringer Ingelheim Japan, Inc., Bristol Myers Squibb Co., Ltd., Chugai Pharmaceutical Co., Ltd., Eisai Co., Ltd., Eli Lilly Japan K.K., GlaxoSmithKline K.K., Kissei Pharmaceutical Co., Ltd., Oxford Immuotec, Pfizer Japan Inc., and Teijin Pharma Ltd. MH is a consultant for AbbVie, Boehringer-ingelheim, Kissei Pharmaceutical Co., Ltd. and Teijin Pharma.